The value of a good idea : protecting intellectual property in an information economy. - Loberg, Kristin (Silver Lake Pub., 2004)
The popularity of the Internet has seen an explosion in disputes over intellectual property issues. This book gives business people the tools for fighting these battles effectively. Starting with a review of the legal concepts that define intellectual property, this book offers clear and useful insights into how these concepts work in the real world. It explains complex (even to legal experts) issues like fair use, infringement, joint authorship and permissions in terms that lay people can comprehend. Readers will understand how to build and protect commercial ideas ... and how to use existing o.
"The Silver Lake Editors who worked on this book include Kristin Loberg [and others]."--Acknowledgments.
Includes index.
Keywords: Intellectual property -- United States.; Trademarks -- United States.; Patents -- United States.; Copyright and electronic data processing -- United States.; Information superhighway -- Law and legislation -- United States.; Propriété intellectuelle -- États-Unis.; Marques de commerce -- États-Unis.; Droit d'auteur et informatique -- États-Unis.; LAW -- Administrative Law & Regulatory Practice.; Copyright and electronic data processing; Information superhighway -- Law and legislation; Intellectual property; Patents; Trademarks; United States